Using High Resolution Melting Method for Detecting Nucleotide Polymorphisms of STK11 Gene Germline in Patients with Digestive System Cancers - Hosseini, Seyed Jamal; Nazemi, Ali; Hashemi, Mehrdad; Miri Nargesi, Mirsaed; Sharirfi, Sharashout; Shaveisi Zadeh, Farhad; Karaminia, Ali Asghar; Movafagh, Abolfazl (Asian Pacific Journal of Cancer Biology, 2016)
Background and Objective: High resolution melting (HRM) analysis is a technique to measure decrease of fluoresce, caused by discharge of the dye, throughout DNA thermal melting gradient process. STK11 gene encodes one of cellular serine-threonine kinase proteins that regulates cellular polarity. It also acts as tumor suppressor protein. Mutations of germline in the gene is coincident with Peutz-Jeghers syndrome and potential of developing a variety of neoplasia. Methodology: In an experimental study, genome DNA of 56 patients with digestive system cancer was extracted. Afterward, nucleotide changes over the gene were examined using Real-time PCR and High resolution melting (HRM). Findings: Nucleotide screening using HRM technique revealed two types of SNP in introns 6 & 7 in 10 patients. Four patients showed homozygous C/T nucleotide changes [cluster id/dsSNP/rs9282860] in intron 6 and six patients showed heterozygous C/G nucleotide changes [cluster id/dsSNP/rs2075607] in intron 7. Comparison of HRM results with sequencing results indicated 100% conformity. Conclusion: Although no mutation was observed in exon section of the gene, primary screening of STK11 gene to diagnose unknown nucleotide changes of germline and somatic in patients with neoplasia using HRM was feasible, easy, and cost effective.